Modern planning and design methods in improving the comfort and safety of pedestrian traffic (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The reconstruction of Ukrainian cities is proposed to be carried out taking into account the high level of motorization of the population in the future, using methods of planning influence and design methods on the speed of traffic in the development of master plans. It is proposed to take into account such criteria as horizontal and vertical requirements for the route, traffic volume, design speed, sight distance, transverse elements, intersections and markings.The author describes the method of "traffic calming", which includes the principle of organizing traffic in the territory by means of diversionary highways; transit traffic is transferred; the conflict between service vehicles, cars of people living in the territory, and pedestrians is resolved by reducing the speed of transport to 35-15 km per hour; pedestrians and public transport are given priority, and schemes for organizing the redevelopment of the intersection are developed. Traffic calming measures help to achieve the goals that can be summarized as two main ones: improving safety and improving the environment. The space of traffic calming streets is rebuilt in such a way that cars traveling along it do not have a direct path to reach objects located there. To achieve this, measures are taken such as narrowing the roadway, curving it by gradually approaching the sides of the street space, and using a special pavement to allow pedestrians to distinguish between areas intended for stationary and moving vehicles.In addition, especially for large cities, the improvement of urban traffic consists in creating a more attractive living environment, as well as safer conditions for citizens to stay and children to play indoors, which is achieved by design methods in the use of decorative asphalt concrete pavement. All components (from unique equipment that heats the asphalt to special coatings) are designed to solve a range of problems in the decorative design of the urban landscape and give unlimited creative freedom to architects and designers. The use of decorative asphalt has an undeniable cost advantage over paving slabs or stone. Decorative asphalt pavement can be produced on existing asphalt concrete. This can provide significant cost savings in its application. The asphalt concrete base provides excellent stability and durability, as well as maintainability of the pavement in comparison with such as road stone, tiles, etc.
Keywords: Planning methods; asphalt pavement design; traffic calming; pedestrian safety; traffic speed; traffic management; residential streets; highways